Dendrite-Free Lithium Deposition via a Superfilling Mechanism for High-Performance Li-Metal Batteries - Wang, Qian (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.